คุณภาพและอัตลักษณ์ของบัณฑิตคณะพยาบาลศาสตร์ มหาวิทยาลัยอีสเทิร์นเอเชียที่สำเร็จการศึกษา ปีการศึกษา 2553 - หาญยุทธ, อรนันท์; รัตนะถาวร, รัชยา (วารสารวิชาการมหาวิทยาลัยอีสเทิร์นเอเชีย ฉบับวิทยาศาสตร์และเทคโนโลยี (Online), 2014)
การวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาคุณภาพบัณฑิตตามกรอบมาตรฐานคุณวุฒิระดับอุดมศึกษา สาขา พยาบาลศาสตร์และศึกษาอัตลักษณ์ของบัณฑิตที่สำเร็จการศึกษาจากคณะพยาบาลศาสตร์ มหาวิทยาลัยอีสเทิร์น เอเชียปีการศึกษา 2553 ตามความคิดเห็นของบัณฑิตพยาบาลและผู้ใช้บัณฑิต กลุ่มตัวอย่าง ประกอบด้วย ผู้บริหาร และพยาบาลประจำการที่ปฏิบัติงานในโรงพยาบาลเดียวกันกับบัณฑิตที่สำเร็จการศึกษาจากคณะพยาบาลศาสตร์ มหาวิทยาลัยอีสเทิร์นเอเชียปีการศึกษา 2553 จำนวนทั้งหมด 162 คน เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูล เป็นแบบสอบถามที่ผู้วิจัยสร้างขึ้น สถิติที่ใช้ในการวิเคราะห์ได้แก่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐานและ t-test ผลการศึกษาพบว่า ผู้ใช้บัณฑิตมีความพึงพอใจต่อคุณภาพบัณฑิตตามกรอบมาตรฐานคุณวุฒิระดับปริญญาตรี สาขาวิชาพยาบาลศาสตร์ทั้ง 6 ด้านอยู่ในระดับมาก = 4.34 และด้านที่มีความพึงพอใจสูงสุดคือด้านคุณธรรม จริยธรรม = 4.49 ในส่วนของคุณลักษณะบัณฑิตตามตามอัตลักษณ์บัณฑิต ผู้ใช้บัณฑิตมีความพึงพอใจทุกด้าน อยู่ในระดับมาก = 4.40 และด้านที่มีความพึงพอใจมากที่สุดคือด้านประสิทธิภาพและจริยธรรม = 4.61 ความคิดเห็นของบัณฑิตและผู้ใช้บัณฑิตต่อคุณภาพบัณฑิตตามกรอบมาตรฐานคุณวุฒิระดับอุดมศึกษา สาขา พยาบาลศาสตร์และคุณลักษณะบัณฑิตตามอัตลักษณ์ในแต่ละด้าน ไม่มีความแตกต่างกันมีนัยสำคัญทางสถิติ ที่ระดับ 0.05 Quality and Identity of Graduated Nurses of School of Nursing, Eastern Asia University in Academic Year 2010 The purposes of this research were to study the quality of graduates by Thai Qualifications Framework for Higher Education in Nursing and to study the characteristics of the graduates from the School of Nursing, Eastern Asia University in Academic Year 2010. The sample consisted of 162 nursing managers and staff working in the same hospitals with the graduates who graduated from the School of nursing, University of Eastern Asia in academic year 2010. The instruments used to collect the data were questionnaires developed by the researchers. The statistics used to analyze the data were percentage, mean, standard deviation and t-test. The results showed that supervisons were satisfied with the quality of the graduates by Thai Qualifications Framework for Higher Education in Nursing of six domains at high level ( = 4.34), the ethics and moral domain had the most satisfaction ( = 4.49). According to the characteristics of the graduates, supervisors were satisfied with all aspect at high level ( = 4.40), the Efficiency and ethics was the most satisfaction ( = 4.61). Comparing the opinions between the supervisors users and the graduates by the Higher Education Qualifications Framework and the identity of the graduates of each side, no differences were statistically significant.